A critical review on application of secure multi party computation protocols in cloud environment - Vijaya Kumar, A; S. S. Reddy, L (International Journal of Engineering and Technology, 2018)
Security is the essential entity of the digital computations in the internet world. Many internet and mobile applications require private data inputs from different clients for data analysis. Now a days many of the Mobile Apps collect the sensitive user data for analysis may be without knowledge of users. Secure Multi Party computation enables distributed users to share their private inputs to a third party which computes a common function over these inputs and the collaborative outcome shared to the user. It is very essential in many engineering, medical and financial sectors where privacy of the sensitive data provided by the user. Many medical researchers require sensitive patientâ€™s data for typical diagnosis. This paper detailed the origin for SMC which is secret sharing. It discussed the evolution of two party computation to secure multiparty computation. Several protocols and their pros and limitations are described. Cloud computing changed the way SMC was interpreted by earlier works. Cloud provides all the computations as a service basis is used to drastically reducing the communications overhead of the SMC. Our contribution is focused on evolution from conventional SMC with towards Secure Multiple Computation in collaboration with the cloud. The works focuses on the research issues to be addressed because of the untrustworthy nature of the cloud. A comparative analysis of different approach of SMC is presented. The comparative study details the open issues like transparency, public data auditability in SMC with cloud architecture.Â